PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DI KELAS IV SDN 03 GERAGAHAN KABUATEN AGAM - Anggi Putri Relisa; Ari Suriani; elfia sukma; Nana Fauzana Azima; Aissy Putri Zulkarnain (STKIP Subang, 2026)
This study was motivated by the low level of reading comprehension skills among students learning Indonesian. This is because teachers have not yet optimally utilized appropriate learning models in the learning process. This study aims to describe the improvement in students' reading comprehension skills using the Cooperative Integrated Reading and Composition (CIRC) model in grade IV at SDN 03 Geragahan, Agam Regency. This research is a classroom action research (CAR) using a qualitative and quantitative approach. The research was conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection. The subjects in this study were teachers and students in the fourth grade of SDN 03 Geragahan, totaling 24 people, consisting of 12 female students and 12 male students. The results of the study show an improvement in cycle I, starting with the results of the teaching module planning analysis: a) the teaching module showed an average of 89.58% (B) in cycle I, increasing to 95.83% (SB) in cycle II, b) the implementation of the teacher aspect in cycle I was 81.48% (B), increasing to 92.59% (SB) in cycle II, while the implementation of student aspects in cycle I was 77.77% (C) and increased to 92.59% (SB) in cycle II, c) the assessment of students' reading comprehension skills in cycle I obtained an average of 78.27 (C) and cycle II obtained an average score of 93.24 (B). It can be concluded that the Cooperative Integrated Reading and Composition model can improve students' reading comprehension skills in Indonesian language learning in fourth grade elementary school.